2020
DOI: 10.1111/jac.12408
|View full text |Cite
|
Sign up to set email alerts
|

High night‐time temperature during flowering and pod filling affects flower opening, yield and seed fatty acid composition in canola

Abstract: Winter canola (Brassica napus L.) is highly sensitive to increasing temperatures during the reproductive and pod‐filling stages. Although the impact of high day‐time temperature stress on yield and quality has been documented in canola, similar information under high night‐time temperature (HNT) stress is not available. Using six hybrids and four open‐pollinated cultivars, we observed a marked shift in peak flowering towards earlier, cooler hours of the morning under HNT. Averaged across two independent experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 86 publications
2
32
0
Order By: Relevance
“…Night temperatures are also critical to the impact of heat stress treatments. High night temperatures during reproductive growth reduced grain yield in canola (Pokharel et al, 2020), and similar observations were made in rice (Bheemanahalli et al, 2017;Coast et al, 2015), quinoa (Lesjak & Calderini, 2017), wheat, and barley (García et al, 2015). Seed set, grain number, and grain yield in winter wheat declined when both daytime (35°C) and night-time (24°C) temperatures were high (Narayanan et al, 2015).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Night temperatures are also critical to the impact of heat stress treatments. High night temperatures during reproductive growth reduced grain yield in canola (Pokharel et al, 2020), and similar observations were made in rice (Bheemanahalli et al, 2017;Coast et al, 2015), quinoa (Lesjak & Calderini, 2017), wheat, and barley (García et al, 2015). Seed set, grain number, and grain yield in winter wheat declined when both daytime (35°C) and night-time (24°C) temperatures were high (Narayanan et al, 2015).…”
Section: Introductionsupporting
confidence: 66%
“…This suggests that lower night-time temperatures may partially compensate for moderate levels but not for high levels of transient daily heat stress. Pokharel et al (2020) found that high night-time temperature (20°C) significantly reduced pod numbers (22%) and total seed yield (40%) in canola compared to cool night-time temperature (15°C) when the daily maximum was 23°C. Dreccer et al (2018) also found that higher minimum temperature after flowering was associated with lower canola seed yield across four major production zones in the 2009-2013 national variety trials in Australia.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Heat stress also negatively affects photosynthetic capacity, respiration, water balance, biomass accumulation and even oil quality‐related attributes (Kaushal et al., 2016; Mayer et al., 2014). The resultant yield and quality decreases due to heat stress ultimately reduce the economic returns and the global supply of canola oilseed (Koscielny, Gardner, et al., 2018; Pokharel et al., 2020; Wu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Canola plants also experience heat stress at different phenological stages, such as the early inflorescence emergence stage where flower bud development is affected, or the late grain filling stage where the pod filling process is restricted (Gan et al., 2004; Pokharel et al., 2020; Prasad et al., 2017; Singh et al., 2013). Early exposure to heat stress before flowering may have little effect on pollen viability and final pod fertility in canola, but may reduce photosynthesis and biomass accumulation, enhance plant respiration and carbohydrate loss during the plant life cycle and lead to the alteration of plant morphology and even yield loss (Siebers et al., 2017; Suraweera et al., 2020; Wu & Ma, 2018).…”
Section: Introductionmentioning
confidence: 99%